THE CHARACYER OF FATHER IN THE WORKS AND LIFE OF WILLIAM AND ARAM SAROYAN - Yepremyan , L. K. (Modern Psychology, 2019)
The article considers the complicated relationship between the father and the son, William and Aram Saroyan influenced by the "ghost" of grandfather, Armenak Saroyan of Bitlis, in the view of psychoanalysis. The studied material’s the memoir by A.Saroyan named "The Last Rites", "Armenak of Bitlis"(from "Letters from 74 rue Taitbout") and "Papa You're Crazy" by W.Saroyan. The purpose of the author is to expose the personal drama of the great Armenian writer that is the intergenerational transmission of the trauma caused by the Armenian Genocide. Orphaned at an early age, William shifts onto his newborn son's shoulders the expectations from the "ghost" of his dead father following him, thus making it impossible to form and assert his paternal position.
Keywords: transgenerational trauma, psychoanalysis, Aram Saroyan, William Saroyan, Edvard Mirzoyan